Mainstreaming climate change in policy frameworks for community-based natural resource management in a semi-arid savannah environment: case study of Botswana - Chikuta, Oliver; Kupika, Olga L.; Nthoi, Olivia (Frontiers in Sustainable Tourism, 2024)
The main aim of this paper is to assess the extent to which the climate change agenda has been mainstreamed into the policy framework of Botswana's CBNRM program. Specific objectives were to (i) to document the impacts of climate change on CBNRM related initiatives in Botswana (ii) to determine the relationship between climate parameters ( temperature and rainfall) and extreme events (drought and extreme heat) and visitor trends in Botswana and the Okavango delta (iii) to establish a historical correlation between evolution of climate change policy and CBNRM policy and vice versa, policy initiatives, programs, strategies and projects in Botswana (iv) to explore the extent to which international, regional, national, and local climate policies mainstream CBNRM and tourism issues and vice versa (v) to explore the challenges and opportunities related to climate change and CBNRM, with a particular focus on adaptation and mitigation initiatives.This paper mostly used qualitative approaches (desktop review of policy documents and scholarly articles) as well as secondary quantitative data (time series data) to explore the evolution of CBNRM in Botswana, providing an overview of its structure, policy initiatives, programs, and projects and how these correspond with the climate change issues. A scoping review was conducted to identify relevant studies on the impacts of climate change on CBNRM initiatives published between 1992 and 2023. A total of 50 articles were identified to answer the research questions: (1) What evidence is available regarding the impacts of climate change on CBNRM initiatives? The paper further examines how climate change-related extreme events, particularly drought, have affected tourism performance over the years. The chapter then zeros down on the effects of climate change on CBNRM initiatives, the challenges, threats, and opportunities, and the mitigation and adaptation strategies adopted by the CBNRM projects in Botswana. Findings indicate that climate change-induced events, particularly drought, have affected Botswana's nature-based tourism products. However, it was revealed that although there is no statistically significant correlation between drought and tourism performance, evidence from the literature reveals that drought has impacted tourism in Botswana.